In vitro evaluation of photoprotective potential of the different solvent extracts of Graptophyllum pictum leaves - Khor Poh-Yen, Seow Lay-Jing, Fatin Hanani (Journal of Applied Pharmaceutical Science, 2018)
Natural substances extracted from plants have been gaining attraction as protective agents due to their safety and responsible for multiple biological effects on skins. The present work evaluates the photoprotective potential of different solvent extracts of Graptophyllum pictum (G pictum) leaves, and the comparison of its Sun Protection Factor (SPF) value against photo-stability and thermal-stability under a 21-day of storage process. Preliminary phytochemical screening was also performed. The dried powdered leaves were extracted by cold maceration method, using five different solvent, i.e. methanol, ethanol, chloroform, ethyl acetate and hexane. The SPF of all extracts were analyzed by ultraviolet (UV) spectrophometry. The SPF results of the five types of extracts were found to have significant differences (P < 0.001). Methanol extract displayed the highest SPF value (15.303±0.045), while the lowest SPF value was showed by ethyl acetate extract. SPF reductions of all extracts under sun exposure condition were higher compared to the extracts placed in dark conditions at room temperature. As compared, the ethanol extract displayed better chemical and thermo-stability with higher in vitro SPF at 200 μg/ml. These findings suggested that ethanol was the solvent of choice for yielding high levels of photoprotective ingredients from G. pictum which can be used to formulate effective sunscreen preparations.
Keywords: Solanum sisymbriifolium, Solanaceae, antinociceptive, medicinal plant, pain.